Hypoxia Triggers SENP1 (Sentrin-Specific Protease 1) Modulation of KLF15 (Kruppel-Like Factor 15) and Transcriptional Regulation of Arg2 (Arginase 2) in Pulmonary Endothelium. Issue 4 (April 2018) - Pandey, Deepesh; Nomura, Yohei; Rossberg, Max C.; Hori, Daijiro; Bhatta, Anil; Keceli, Gizem; Leucker, Thorsten; Santhanam, Lakshmi; Shimoda, Larissa A.; Berkowitz, Dan; Romer, Lewis
Abstract : Objective—: KLF15 (Kruppel-like factor 15) has recently been shown to suppress activation of proinflammatory processes that contribute to atherogenesis in vascular smooth muscle, however, the role of KLF15 in vascular endothelial function is unknown. Arginase mediates inflammatory vasculopathy and vascular injury in pulmonary hypertension. Here, we tested the hypothesis that KLF15 is a critical regulator of hypoxia-induced Arg2 (arginase 2) transcription in human pulmonary microvascular endothelial cells (HPMEC). Approach and Results—: Quiescent HPMEC express ample amounts of full-length KLF15. HPMECs exposed to 24 hours of hypoxia exhibited a marked decrease in KLF15 protein levels and a reciprocal increase in Arg2 protein and mRNA. Chromatin immunoprecipitation indicated direct binding of KLF15 to the Arg2 promoter, which was relieved with HPMEC exposure to hypoxia. Furthermore, overexpression of KLF15 in HPMEC reversed hypoxia-induced augmentation of Arg2 abundance and arginase activity and rescued nitric oxide (NO) production. Ectopic KLF15 also reversed hypoxia-induced endothelium-mediated vasodilatation in isolated rat pulmonary artery rings. Mechanisms by which hypoxia regulates KLF15 abundance, stability, and compartmentalization to the nucleus in HPMEC were then investigated. Hypoxia triggered deSUMOylation of KLF15 by SENP1 (sentrin-specific protease 1), and translocation of KLF15 from nucleus to cytoplasm. Conclusions—: KLF15 is a critical regulator of pulmonary endothelial homeostasis via repression of endothelial Arg2 expression. KLF15 abundance and nuclear compartmentalization are regulated by SUMOylation/deSUMOylation—a hypoxia-sensitive process that is controlled by SENP1. Strategies including overexpression of KLF15 or inhibition of SENP1 may represent novel therapeutic targets for pulmonary hypertension. Abstract : Supplemental Digital Content is available in the text.